A Comparison of Protein and mRNA Expression during Development of the Soil Dwelling Prokaryote (S. coelicolor). Issue 14 (29th June 2020) - Pospíšil, Jiří; Strunin, Dmytro; Ziková, Alice; Hubálek, Martin; Vohradský, Jiří
Abstract: In this paper, correlation analysis of protein and mRNA levels in the soil dwelling bacteria Streptomyces coelicolor ( S. coelicolor M145) is presented during development of the population as it grew in liquid medium using three biological and two technical replicates, measured during exponential growth, and its entry into the stationary phase. The proteome synthesis time series are compared with the gene expression time series measured previously under identical experimental conditions. Results reveal that about one third of protein/mRNA synthesis profiles are well correlated while another third are correlated negatively. Functional analysis of the highly correlated groups is presented. Based on numerical simulation, the negative correlation between protein and mRNA is shown to be caused by the difference between the rate of translation and protein degradation.